Zur Peripherie postmoderner Metropolen: Periurbanisierung, Fragmentierung und Polarisierung, untersucht am Beispiel Madrid - Wehrhahn, Rainer (ERDKUNDE, 2000)
The paper investigates to which extent postmodern developments are taking place in the periphery of Madrid. At first, it is proved with the help of socio-demographic and economic data that a process of peripherisation has started in the 1990s, which crosses the borders of the suburban area significantly. This peri-urbanisation is linked with a fragmentation of the periphery, socially as well as economically. The social fragmentation results mainly from differently motivated, selective migration. The intra-regional migrations within Greater Madrid on the other hand are influenced by the socio-economic change, a demographic transformation of the urban population, as well as by changed preference concerning lifestyle. The social fragmentation in Madrid is e.g. expressed by the facts that different kinds of gated communities are being created and that housing estates of first and second homes are being increasingly mixed. The economic fragmentation starts with a new pattern of shopping malls, entertainment centres, factory outlet centres and technology parks in the periphery. The fragmentation as well as new polarisation in the periphery are to a great extent influenced by processes which also occur in other postmodern metropolises, but which are changed in their effect and their dimension due to local peculiarities. However, regarding the still central role of the city of Madrid within the agglomeration, we cannot talk about a dissolution of the city.